Effect of nanocrystals surface modification on organic inorganic hybrid photovoltaics - Chung, Ja Vui. (2010)
Organic based photovoltaics including organic/inorganic hybrid solar cells have been a very attractive topic in recent years. Various ways have been employed to improve the performance of these devices. The surfaces of Cadmium Selenium (CdSe) nanoparticles were modified with small molecules in order to improve photovoltaic performance of hybrid solar cell. Effects of surface modification were studied by Photoluminescence (PL), Ultraviolet-visible Absorption Spectroscopy (UV-vis), Thermal Gravimetric Analysis (TGA), Fourier Transform Infrared Spectroscopy (FTIR) and Transmission Electron Microscopy (TEM). Thiophene-ethylamine (TEA), thiophene-methylamine (TMA) and pyridine (py) were used to replace the original ligand on surfaces of CdSe nanoparticles. Photovoltaic devices were fabricated using these nanoparticles and the performances were doubled after ligand exchange. Highest Incident-Photon-to-electron Conversion Efficiency (IPCE) of 30.7% at 380nm wavelength, 28.9% and 28.6% at 420nm were obtained for CdSe nanoparticles exchanged with pyridine, TMA and TEA respectively. Furthermore, 0.744%, 0.623% and 0.629% of power conversion efficiency were obtained for CdSe-py, CdSe-TMA and CdSe-TEA respectively.